Osmium isotope evidence for two pulses of increased continental weathering linked to Early Jurassic volcanism and climate change - Percival, Lawrence M.E.; Cohen, A.S.; Davies, M.K.; Hesselbo, Stephen P.; Jenkyns, H.C.; Leng, Melanie J.; Mather, T.A.; Storm, Marisa S.; Xu, W. (Geological Society of America, 2016)
Large igneous provinces (LIPs) are proposed to have caused a number of episodes of abrupt environmental change by increasing atmospheric CO2 levels, which were subsequently alleviated by drawdown of CO2 via enhanced continental weathering and burial of organic matter. Here the sedimentary records of two such episodes of environmental change, the Toarcian oceanic anoxic event (T-OAE) and preceding Pliensbachian–Toarcian (Pl-To) event (both possibly linked to the Karoo-Ferrar LIP), are investigated using a new suite of geochemical proxies that have not been previously compared. Stratigraphic variations in osmium isotope (187Os/188Os) records are compared with those of mercury (Hg) and carbon isotopes (d13C) in samples from the Mochras core, Llanbedr Farm, Cardigan Bay Basin, Wales. These sedimentary rocks are confirmed as recording an open-marine setting by analysis of molybdenum/uranium enrichment trends, indicating that the Os isotope record in these samples reflects the isotopic composition of the global ocean. The Os isotope data include the first results across the Pl-To boundary, when seawater 187Os/188Os increased from ~0.40 to ~0.53, in addition to new data that show elevated 187Os/188Os (from ~0.42 to ~0.68) during the T-OAE. Both increases in 187Os/188Os correlate with negative carbon isotope excursions and increased mercury concentrations, supporting an interplay between terrestrial volcanism, weathering, and climate that was instrumental in driving these distinct episodes of global environmental change. These observations also indicate that the environmental impact of the Karoo-Ferrar LIP was not limited solely to the T-OAE.